EFFECT OF ALTERATIONS IN CONVENTIONAL MEDIUM ON LIPID ACCUMULATION AND FATTY ACID CONTENT IN OLEAGINOUS YEASTS - VIPRA VIJAY JADHAV; DIPTI SAMBHAJI SALUNKHE; RAMA KAUSTUBH BHADEKAR (International Journal of Pharma and Bio Sciences, 2012)
Yeast oils have several biotechnological applications such as fatty acid bioconversion, substrate valorization, polyunsaturated fatty acids production, oil polluted water bioremediation, biodiesel etc. Effects of physical and chemical parameters on lipid content in yeasts, therefore, deserve special consideration. In view of this, two oleaginous yeasts viz. Yarrowia lipolytica (NCIM 3589) and Lipomyces lipofera (NCIM 3252) were studied for their lipid producing capacities. We observed 1.6 times increase in lipids (8.0 %) in medium A1 for Y. lipolytica and 1.9 times increase in lipids (2.4 %) in medium A2 for L. lipofera as compared to MGYP. In order to make the medium cost effective, glucose and peptone in MGYP were replaced with local commercial table sugar (LCTS) and urea respectively. Thereby 1.7 fold increase using medium B1 for Y. lipolytica and 2.0 fold increase using medium B2 for L. lipofera as compared to MGYP was achieved. In media B1 and B2, increase in fatty acids (monounsaturated and linoleic acid in both the yeasts and saturated in L. lipofera) was observed as compared to MGYP.